Jokioisten Kedonojankulman Cu-Au -esiintymän fluidisulkeumatutkimukset - Klami, Jarkko (Helsingfors universitet, 2013)
The Kedonojankulma Cu-Au occurrence is situated in the Svecofennian Häme belt in Southern Finland, about 13 km north of Forssa. The occurrence is hosted by a porphyritic tonalite intrusion. The surrounding of tonalite intrusion consist mostly Palaeoproterozoic mafic and intermediate volcanic rocks. The occurrence was found by Geological Survey of Finland in 2006 after regional till-geochemical surveys and diamond drillings. Several features that are typical in most porphyry copper deposits have been identified, such as metal content and metals zoning. Only a few porphyry copper deposits have been found from the Palaeoproterozoic granitoids in the Fennoscandian Shield area. Aim of this study is to exanimate fluid inclusions and determinate is there indication of porphyry copper-type deposit. In many parts of the Kedonojankulma intrusion, early dark quartz-sulfide veins are cutting the host rock. The highest metal grades are in and around quartz-sulfide veins. The samples for laboratory measurements were collected from these dark quartz-sulfide veins. The most important research method was microthermometric studies. Daughter minerals in fluid inclusion were also identified by scanning electron microscope-energy dispersive spectrometry (SEM-EDS). Based on the microthermometric data from four samples, fluid inclusions show a wide variation in salinity about 2 - 45 wt. percent (NaCl equiv.) and homogenization temperatures about 100 - 420 °C. The most common ore minerals were found in porphyritic tonalite as well as daughter minerals inside the fluid inclusions. Evidence of boiling was also observed in a few samples. Fluid inclusion compositions, salinity, daughter minerals, boiling, a magmatic origin of fluids, homogenization behavior and many other factors indicate a porphyry copper-type deposit. Kedonojankulman Cu-Au -esiintymä sijaitsee Etelä-Suomessa noin 13 km Forssasta pohjoiseen Svekofennisellä Hämeen liuskevyöhykkeellä. Esiintymän isäntäkivenä on porfyyrinen tonaliitti-intruusio, jota ympäröi mafiset ja ...